Level of Knowledge, Mother's Perception, and Family Support with Exclusive Breastfeeding - Resty Jayanti; Fenti Dewi Pertiwi; Andreanda Nasution; Siti Walidaturrahmah Alfaeni; Siti Susi (Jurnal Promosi Kesehatan Indonesia, 2025)
Background: The baby's immune system is strengthened by exclusive breastfeeding, thus protecting the baby from various diseases that can endanger his health. To determine the relationship between the level of knowledge, perception, family support, and exclusive breastfeeding.Method: This was a cross-sectional study. This study used the chi-square analysis test. This quantitative research was carried out in the work area of the Sindang Barang Community Health Center between October 2024-March 2025. The samples were collected using an accidental sampling technique. The sample size was determined using the Slovin Formula, resulting in a total of 78 samples. The data used are taken directly using a questionnaire consisting of the variables level of knowledge, mother's perception, and family support.Result: There is a significant relationship between knowledge, positive perception, family support and exclusive breastfeeding with respective p values (0.000; 0.016; 0.000). Based on statistical tests, the OR value for the knowledge variable was also 13.8, which means that mothers with poor knowledge have a 13.8 times greater chance of not providing exclusive breastfeeding than mothers with good knowledge. The OR value for the family support variable is 5.5, which means that mothers who have a negative perception are 5.5 times more likely to not provide exclusive breastfeeding than mothers with a positive perception. The OR value for the family support variable is 26.1, which means that mothers with a lack of family support have a 26.1 times greater chance of not providing exclusive breastfeeding than mothers who receive family support. It can be concluded that there is a significant relationship between knowledge, positive perceptions, family support, and exclusive breastfeeding.